Endangered Animals - Jinny Johnson (Essex Miles Kelly, 2013)
It is a children$1 (Bs non-fiction book that focuses on animals at risk of extinction. It provides a comprehensive look at various species that are endangered and explores the reasons behind their precarious situations.s